A Thrombomodulin Promoter Gene Polymorphism, rs2239562, Influences Both Susceptibility to and Outcome of Sepsis - Watanabe, Eizo; Takasu, Osamu; Teratake, Youichi; Sakamoto, Teruo; Ikeda, Toshiaki; Kotani, Joji; Kitamura, Nobuya; Ohmori, Masaaki; Teratani, Ayako; Honda, Goichi; Hatano, Masahiko; Mayer, Benjamin; et al. (Frontiers in Medicine, 2022)
Objective: Disseminated intravascular coagulation plays a key role in the pathophysiology of sepsis. Thrombomodulin is essential in the protein C system of coagulation cascade, and functional polymorphisms influence the human thrombomodulin gene (THBD). Therefore, we conducted a multicenter study to evaluate the influence of such polymorphisms on the pathophysiology of sepsis. Design: A collaborative case-control study. Setting: A heterogeneous population the intensive care unit (ICU) of each of five tertiary emergency centers. Patients: The study included 259 patients (of whom 125 displayed severe sepsis), who were admitted to the ICU of Chiba University Hospital between October 2001 and September 2008 (discovery cohort) and 793 patients (of whom 271 displayed severe sepsis), who were admitted to the five ICUs between October 2008 and September 2012 (multicenter validation cohort). To assess the susceptibility to severe sepsis, we further selected 222 critically ill patients from the validation cohort matched for age, gender, morbidity and severity with the severely septic patients, but without any evidence of sepsis. Measurements and Main Results: We examined whether the eight THBD SNPs were associated with susceptibility to and/or mortality of sepsis. Higher mortality on severe sepsis in the discovery and combined cohorts was significantly associated with the GG genotype in a THBD promoter SNP (−1748*G/C; rs2239562) (OR 2.709 (1.067–6.877), P = .033 and OR 1.768 (1.060–2.949), P = .028). Furthermore, rs2239562 SNP was associated with susceptibility to severe sepsis (OR 1.593 (1.086–2.338), P = 0.017). THBD G- or C-allele reporter plasmids were transfected, and luciferase activity was determined. THBD, which has the C-allele at −1748, exhibited higher promoter activity in HUVEC, EA.hy926, and THP1 cell lines compared to that of G-allele transfectants (P = 0.019, 0.004, and 0.016). Conclusions: The data demonstrate that rs2239562 SNP influences both outcome and susceptibility to severe sepsis through regulation of the THBD transcriptional activity.